PETA MUTU SATUAN PENDIDIKAN DI INDONESIA (Studi Pilotting Project akreditasi 2020) - Karwono, H; Susetyo, Budi (Jurnal Penelitian Kebijakan Pendidikan, 2021)
The 2020 school accreditation instrument (IASP2020) has changed the paradigm from accreditation as simply fulfilling administrative requirements to performance-based evaluation. IASP2020 focuses on measuring the quality of graduates, the learning process, quality of teachers, and school management. This research aims to examine the roadmap of education quality by type, level and area, and performance quality based on the accreditation components in IASP 2020 and the challenges to attain higher education quality. The data analyzed were the results of the piloting accreditation conducted by Board of National Accreditation for Schools/Madrasas (BAN-S/M) in 2020 on 4817 schools and madrasas. Sample selection was done through quota sampling. The results concluded that the majority of schools were accredited B. Senior High Schools (SMA) had better accreditation rating compared to other levels. In contrast, Elementary Schools/Madrasas (SD/MI) had the fewest A accreditation rating. Quality between provinces vary widely. DKI had the highest percentage of A rating while the lowest is NTT. The teacher quality component had the lowest score compared to the other three components. The factors causing the low quality at SD/MI were the students' low ability to communicate effectively, think critically in problem-solving and the lack of teachers’ initiative to carry out sustainable professional development. The low quality of SMK was due to the lack of graduates who were able to obtain competency certificates from the Professional Certification Institute, the poor management of the production unit/business center/techno park, and the lack of teachers who apply the results of training in the learning process. Instrumen Akreditasi Satuan Pendidikan tahun 2020 (IASP2020) mengubah paradigma penilaian akreditasi dari berbasis pemenuhan administratif menjadi berbasis kinerja. IASP2020 fokus mengukur komponen mutu lulusan, proses pembelajaran, mutu guru, dan manajemen sekolah. Tujuan dari penelitian ini adalah mengkaji peta mutu pendidikan berdasarkan jenis, jenjang dan wilayah serta kinerja komponen mutu dan faktor kendala pencapaian mutu berdasarkan hasil IASP2020. Data yang dianalisis berasal dari hasil piloting yang dilakukan oleh BAN-S/M tahun 2020 terhadap 4817 sekolah dan madrasah. Sekolah sampel pada piloting ini dipilih melalui sampling kuota, yang terwakili di seluruh provinsi, jenjang, dan jenis satuan pendidikan. Hasil analisis menyimpulkan bahwa mayoritas sekolah/ madrasah terakreditasi B. SMA memiliki peringkat akreditasi lebih baik dibandingkan dengan jenjang lainnya, sebaliknya SD/MI memiliki jumlah peringkat akreditasi A terkecil. Mutu antar provinsi sangat bervariasi. Provinsi DKI memiliki jumlah peringkat A terbanyak sedangkan terendah adalah NTT. Komponen mutu guru memiliki skor paling rendah dibandingkan tiga komponen lainnya. Faktor penyebab rendahnya mutu jenjang SD/MI adalah masih rendahnya kemampuan siswa dalam berkomunikasi secara efektif, berpikir kritis dalam pemecahan masalah, dan inisiatif guru melakukan pengembangan profesi berkelanjutan. Rendahnya mutu SMK terletak pada kurangnya lulusan yang memperoleh sertifikat kompetensi dari Lembaga Sertifikat Profesi, pengelolaan unit produksi/business center/technopark belum baik, dan rendahnya guru yang menerapkan hasil pelatihan dalam proses pembelajaran.